Modeling the electrical characteristics of Si/organic solar cell - Lee, Jie Xin (2016)
As the demand for renewable clean energy increases, extensive research has been directed towards photovoltaics (PV) energy owing to its abundance and availability. Despite that the conventional crystalline bulk silicon (Si) solar cells are highly efficient and reliable; the costly Si material and fabrication processes render them not cost-effective as fossil fuels. To address the cost issue, hybrid solar cells based on Si and organic materials have emerged as promising candidates to leverage on the advantages of the highly efficient Si material and the low cost and flexibility offered by organic materials. In this report, the performance of Si/PEDOT:PSS solar cell is investigated using both theoretical simulation and experimental fabrication of the cells. The simulation was carried out using the Silvaco software to study the voltage, current and the open-circuit voltage, short circuit current, fill factor and efficiency of the hybrid cells as a function of their device parameters that include the Si absorber thickness and its doping. Furthermore, Si/organic solar cell are fabricated and the experimentally measured performance is compared and contrast with the simulation results. We also attempted to adjust the simulation software parameters to fit to the actual data, so that the actual device parameters of the cells can be deduced.